How Does the Three-factor Model Perform and What Explains its Performance? Empirical tests on Swedish stock portfolios - Björck,Daniel (2023)
In this study the three-factor model of Fama and French (1992; 1993) is evaluated on portfolios of Swedish stocks. Both a cross-section and time series approach are used to evaluate the model. The results show that beta, size, and book-to-market are significant variables in explaining excess returns of Swedish stock portfolios. The three-factor model can explain variations in stock returns on the Swedish market, though the performance is lower than when using the model to explain excess returns in for example the US, Europe, and Japan (Fama & French, 1992; 1993; 2012). In addition to evaluating the performance of the three-factor model, this study also analyses what affects the performance and the coefficients of the model on the Swedish stock market. This is done by testing a number of macroeconomic variables related to the Swedish market to see whether they have significant relationships with the performance of the three-factor model and the effects of the model’s independent variables. The macroeconomic variables included in these tests are GDP growth, inflation rate, oil prices, change in money supply, stock market returns, industrial production growth and unemployment rate. This study concludes that change in money supply is a significant variable in explaining the performance of the model, with a negative relationship. In explaining the coefficients of beta, size and book-to-market, GDP growth is a significant variable in all cases, while industrial production growth is significant in explaining the size and beta coefficients.
Keywords: Three-factor model; stock returns; Swedish stocks; CAPM